Case report: A novel compound heterozygous variant in the COL4A3 gene was identified in a patient with autosomal recessive Alport syndrome - Chen, Sha; Zhang, Yufeng; He, Jinjin; Yang, Dingwei (Frontiers in Genetics, 2024)
Alport syndrome (AS), a hereditary kidney disease with a high risk for renal failure, is attributed to pathogenic variants in genes COL4A3, COL4A4, and COL4A5 that encode type IV collagen. Next-generation sequencing (NGS) is increasingly applied to the diagnosis of AS, but complex genotype–phenotype correlation, that is, identifying the significance of variants, is still a huge clinical challenge. In this study, we reported the case of a 27-year-old Chinese woman with a family history of hematuria and proteinuria. Notably, the proband is the only one in her family with renal insufficiency. NGS was performed in this family, and it was revealed that the proband was a compound heterozygote for two variants in the COL4A3 gene: c.2990G>A inherited from her father and c.4981C>T inherited from her mother. We modeled the spatial structure of the corresponding protein and assumed that structural abnormalities led to the breakdown of type IV collagen networks, a major component of the glomerular basement membrane. Thus, the proband was diagnosed with autosomal recessive AS, characterized by severe defects of the glomerular basement membrane. Hence, the proband showed a loss of renal function. This case presentation emphasizes the importance of NGS for AS diagnosis and introduces a novel genotype of AS.